EFISIENSI PERBANKAN DI INDONESIA DAN PENGARUHNYA TERHADAP RETURN SAHAM DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS ( DEA ) - Rina Sari Qurniawati (Benefit: Jurnal Manajemen dan Bisnis, 2013)
The purpose of this study was to analyze bank efficiency listed in Indonesia Stock Exchange (IDX) and to empirically determine the effect of bank efficiency listed in BEI toward stock performance reflected in stock returns. The sampling is bank listed in IDX from 2004 until 2008. DEA is used to measure the bank efficiency from each Decision Making Units  (DMUs),which is obtained as the maximum weight ratio of outputs and inputs. The result of banks efficiency using DEA approach indicated that most of Bank in Indonesia is efficient. Only 6 banks from 16 banks which have not yet reached the efficiency score over the 5 years. Meanwhile, the regression test did not revealed any effect of the bank efficiency in Indonesia toward stock return.